Effects of Emerging-Economy Firms’ Knowledge Acquisition from an Advanced International Joint Venture Partner on Their Financial Performance Based on the Open Innovation Perspective - Choo Yeon Kim; Eun-Hwa Seo; Canisha Booranabanyat; Kwangsoo Kim (Journal of Open Innovation: Technology, Market and Complexity, 2021)
Although emerging-economy firms (E-E firms) must have a keen interest in improving their performance by utilizing knowledge transferred from their advanced international joint venture (IJV) partner, there has been little research on the performance implications of E-E firms’ knowledge transferred from their advanced IJV partner. So, drawing on open innovation and organizational learning perspectives, we examine whether, how, and when E-E firms’ knowledge acquisition from their IJV partner has a positive impact on their financial performance. Based on data collected from 127 Thai manufacturing firms with a local IJV partnered with an advanced overseas firm, our results reveal that E-E firms’ knowledge acquisition from their IJV partner has an overall positive influence on their financial performance in terms of growth and profitability. Our results further show that innovation performance mediates the relationship between E-E firms’ knowledge acquisition and their financial performance based on a moderated mediation analysis including innovation performance as a mediator and absorptive capacity as a moderator. It is also found that the positive mediation effect of innovation performance is more pronounced in the presence of higher absorptive capacity than otherwise. That is, our results show that even among E-E firms which have acquired much knowledge from their IJV partner, those with higher absorptive capacity achieve better innovation performance than those with lower absorptive capacity, and improved innovation performance subsequently contributes to producing superior financial performance. The key conclusions, implications, and limitations of our study are presented based on these findings.